Edible flowers: a review of the nutritional, antioxidant, antimicrobial properties and effects on human health - Fernandes, Luana (2017)
Edible flowers have been traditionally used for human consumption in various cultures. They improve the appearance, taste and aesthetic value of food, aspects that consumers appreciate, justifying the increasing trend of fresh top quality flowers’ sales worldwide. However, consumers also demand foods with beneficial health properties, in addition to the nutrients they contain, looking for functional qualities such as antioxidant and antimicrobial properties. This review summarizes the data of more than 100 studies performed until now on edible flowers, focusing on nutritional, antioxidant and antimicrobial activities, as well as health effects. This review provides valuable information on edible flowers in order to better characterize them and to increase their popularization among the food industry and consumers.